Assessment of genetic diversity among India Ginseng, Withania somnifera (L) Dunal using RAPD and ISSR markers - Khan, Shahana; Shah, Rehana Anjum (Research in Biotechnology, 2016)
Withania somnifera is commonly known as Indian Ginseng or Ashwagandha which is listed highly medicinal plant in Ayurveda for its wide range of medicinal use. Genetic diversity among 16 genotypes of Withania somnifera collected from four different regions viz. Lucknow, Nimuch, Karnataka and Mumbai was studied using RAPD and ISSR techniques. The ISSR and RAPD together produced 89 bands across 16 genotypes of W. somnifera of which 39 were polymorphic showing 47.89% polymorphism. Over 99% of the RAPD and ISSR fragments were reproducible in the present experiment. There was 90% uniformity within the population. The neighbor joining tree also confirmed a clear grouping and differentiation based on populations of origin i.e. samples were grouped on the basis of their regions of origin. The dendrogram reveals that outgroup of W. somnifera Karnataka origin are evolutionarily related to W. somnifera Nimuch group varieties and W. somnifera Lucknow and Mumbai group varieties are evolutionarily closely related. Within population analysis of Lucknow and Nimuch location showed two sub groups of two lines each showing slight diversity. Plants from Karnataka and Mumbai region show less diversity within population.